Step-by-step explanation:
- 3x+5y=7b equation 1
- 2x+4y=1
2x=-4y+1
- x=(-4y+1)/2
- x=(-4y+1)/2 in equation 1
3×(-4y+1)/2+5y=7b
(-12y+3)/2+5y=7b
(-12y+3+10y)/2=7b
(-12y+3)/2=7b
-12y+3=14b
-12y=14b-3
- y=3-14b/12
- y=3-14b/12 in x=(-4y+1)/2
x=(-4×{3-14b/12}+1)/2
x=(-3+14b)/3+1/2
x=14b/3×1/2
<span>3x</span>²<span> + 23x − 8 = 3x</span>² + 24x - x - 8 = 3x(x+8) - (x+8) = (x+8)(3x-1)
Answer:
Step-by-step explanation:
20 increased to 22
20/22= 10%
10% of 20.00 is $2.00
2+20 = 22
These words are represented as homophones as they sound alike but have the different meanings.
Dear, there is no solution to this equation